Assessing Retail Biomass Electricity Efficiency in Japan: Focus on Average Cost and Benefit - Noriko Irie (MDPI AG, 2021)
Biomass utilisation has been one of the most pertinent topics in the field of sustainability. An example of biomass resource usage is renewable electricity (REL) using bioresources (Bio-REL). Although Bio-REL is widely disseminated globally, existing research suggests that it may be less economically efficient than other REL sources. The cost of Bio-REL has not changed in recent years, but the cost of solar or photovoltaic (PV) REL has been significantly reduced. Some studies also assert that retail Bio-REL is preferred less than PV-REL. As this is not well established in the literature, this study analysed the average levelised costs of energy (LCOE) and preferences for retail Bio-REL and PV-REL while focusing on the case of Japan. The results indicate that the average LCOE of retail Bio-REL was 1.4 times greater than that of PV-REL, while the willingness to pay (WTP) for Bio-REL was about half. The analysis has considerable relevance for countries other than Japan with comparative cost and preference for both REL sources. The research raises an important issue regarding the efficiency of the strategy of REL dissemination and proposes that a comprehensive economic analysis of the social benefits of Bio-REL be conducted.